الفروق الفردية بين المتعلّمين - Dian Rizky Amalia (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
This article addresses the reality learning showed us that they did not agree to a significant difference in how much success end. Here psychologists assert that differences in learning outcomes need to go back to the individual differences among student. Cleared that the use of the most skilled educated is in fact different from the strategies that will be used by the least educated skill. Motivation refers to the desire to achieve aims, and effort is given in this way, and satisfaction for the task. There are ways and methods consistent with those that may not fit with the others to the presence of differences in ability and inclination, that the most successful strategy chosen by the teacher after studying and evaluating strategic wiyh all student, can even be used for the approval of a learning program learners. In accordance with the needs of society and the interests of any individual discovery and development capabilities. Keywords: individual differences, cognitive factors, emotional factors